NEW DATA ON LOOSE FORMATIONS OF VARAGAJUR, TAVUSH, AND KHNDZORUT RIVER BASINS (REPUBLIC OF ARMENIA) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
New data on the results of field mapping and laboratory analyses of loose formations in the northeastern part of the Tavush Region are presented. The main attention is paid to dense, microporous, light yellow, dusty, and mostly without inclusions of stone material, usually structureless sandy loams, loams, clays, and diatomites with a total thickness of up to 25–30 m, widely distributed in the lower reaches of the Varagajur, Tavush and Khndzorut River basins. They lie on different forms of relief, overlap the alluvium of the second and third terraces, ancient removal cones, bedrocks, can be traced high up the slopes to an absolute height of 1400–1500 m, and resemble loess-like loam in appearance. They are taken by us for lake-dam deposits treated by the processes of hypergenesis. These deposits are characterized by increased carbonate content (up to 8.02–10.58%), they contain new formations in the form of carbonate aggregates with a diameter of 2–3 cm to 10 cm and contain shells of foraminifera, characteristic of limestone common here. Of the modern species, there is Napaeopsis hohenackeci, widespread throughout the Transcaucasia and characteristic of arid conditions. The physicomechanical properties, chemical composition, and geochemical coefficients of loess-like loams, as well as ancient weathering crust formed on limestones in the same area are considered. In the granulometric spectrum of loams and clays of loess-like formations, the highest content falls on a fraction of 0.05–0.01 mm (38.96 and 31.69%), and in clays of weathering crust – on a fraction < 0.005 mm (46.93%). Weathering crust clays are also distinguished by their greater plasticity – the number of their plasticity is 23.1. The weathering crust contains more slow-moving oxides (SiO2, Al2O3, Fe2O3) and less CaCO3 than loess-like loams. The higher CaCO3 content in loess-like loams confirms their transformation under arid conditions with the corresponding accumulation of calcium carbonate. The differences in the conditions of formation of the considered loose formations by the ratio of chemical components – their geochemical coefficients are also revealed. Low values of the coefficients Al2O3/TiO2, CaO/MgO, (CaO+Na2O+K2O)/Al2O3 in the clays of the weathering crust indicate their greater weathering than loess-like loams. At the same time, weathering crust clays are characterized by higher oxidetion coefficients of Fe2O3/FeO, decomposition of Fe2O3/MgO, and hydration of H2O–/(MgO+CaO+Na2O+K2O). They also contain more rare (R=La+Y+Yb+Nb+Ta), small petrogenic (S=Be+Li+B+Rb), and metallic elements (M=Cu+Pb+Zn). It is noted that the geochemical coefficients of loose accumulations make it possible to identify the climatic conditions of their formation.
Keywords: loess-like loam; clay; geochemical coefficient; terrace; river basin